Phytochemical Screening, Antioxidant, and Antimicrobial Activities of Seven Underinvestigated Medicinal Plants against Microbial Pathogens - Borel Ndezo Bisso; Roland Njikang Epie Nkwelle; Roland Tchuenguem Tchuenteu; Jean Paul Dzoyem (Hindawi Limited, 2022)
Background. Plants are a rich source of therapeutic compounds that have tremendous applications in the pharmaceutical industry. This study aimed to identify the phytochemicals present in the seven selected medicinal plants as well as their antioxidant and antimicrobial activities. Methods. Phytochemical screening, total phenolic, and flavonoid contents were determined using standard methods. The antioxidant activity of plant extracts was determined using 2, 2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl (OH), and nitric oxide (NO) radical scavenging assays. The antimicrobial activity of the plant extracts was determined by the broth microdilution method. Results. The results of phytochemical analysis showed the presence of phenols, flavonoids, and steroids in all plant extracts. The extract of Psychotria peduncularis showed the highest total phenolic and flavonoid contents (5.57 ± 0.22 mg GAE/g and 1.38 ± 0.06 mg QE/g, respectively). All plant extracts showed very strong antioxidant activity against DPPH and NO radical scavenging with IC50 values ranging from 0.55 to 49.43 µg/mL and 0.65 to 13.7 µg/mL, respectively. The extracts of Tristemma mauritianum and P. peduncularis displayed significant antibacterial activity with MIC values ranging from 16 to 1024 µg/mL. T. mauritianum extract showed bactericidal activity against all tested species. The extracts of Alsophila manianna and P. peduncularis showed significant antifungal activity (MIC = 64 µg/mL) against Candida albicans strain. Conclusion. The screened extracts of medicinal plants used in our study can be used as potential antioxidant and antimicrobial agents, and resources for the development of new drugs.